Extending The Service Life Of Asphalt Pavements Via Phase Change Materials A Systematic Literature Review - Ngo, Uk Doong (Universiti Sains Malaysia, 2022)
Phase Change Materials (PCMs) that were applied in the asphalt pavement is gaining attention on improving the road durability. PCMs act as one of the repair agents when cracking occurs at a certain temperature. PCMs has been applied in cold climate countries such as China where thermal cracking problems often occur. This makes it possible to solve the thermal cracking problem by applying the PCMs as the thermal energy storage in asphalt pavements to regulate the temperature in order to avoid thermal cracking on the asphalt pavements. To select the optimum and relevant PCMs, parameters such as thermal stability, latent heat capacity and phase change properties must be taken into consideration, study and analysis precisely. This systematic literature review (SLR) can be used as a reference for readers and researchers on PCM in terms of the potential of the materials used, mechanisms, and behaviour of PCM in asphalt pavements. The objective of this SLR is to identify the types of PCM that can be used in asphalt pavement, analyse the various types of mechanism and the behaviour of PCM as a repair agent to improve road durability. This review is intended in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) in order to avoid any bias and enhance the dependability of the retrieved data. This systematic literature review was conducted based on findings from studies from the last 10 years (2013-2022) in the field of asphalt technology. It is hoped that this SLR can provide guidance to researchers to further the study related to PCMs in more depth and expanded to tropical countries.